2012
DOI: 10.1103/physreve.85.061916
|View full text |Cite
|
Sign up to set email alerts
|

Optimal diffusion coefficient estimation in single-particle tracking

Abstract: Single-particle tracking is increasingly used to extract quantitative parameters on single molecules and their environment, while advances in spatial and temporal resolution of tracking techniques inspire new questions and avenues of investigation. Correspondingly, sophisticated analytical methods are constantly developed to obtain more refined information from measured trajectories. Here we point out some fundamental limitations of these approaches due to the finite length of trajectories, the presence of loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
371
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 253 publications
(378 citation statements)
references
References 39 publications
4
371
1
2
Order By: Relevance
“…For example, the anomalous vs. standard diffusion question can be hard to resolve using a single trajectory when one only has access to a time series spanning ≈ 1 − 5 s and measurement noise is significant relative to thermal fluctuations [18][19][20] (this noise is sometimes referred to as "localization noise" [22] in the SPT literature). Robustness against questionable localization noise assumptions is desirable since this noise is difficult to accurately quantify in many experiments [14,[22][23][24] despite its potential heavy influence on parameter estimation, hypothesis testing, and other model diagnostics [25][26][27]. In addition, methods not requiring ensemble averaging (i.e., those capable of carrying out tests with a single trajectory) are of interest since the effective dynamics experienced in vivo can be heterogeneous due to varying local micro-environments [14,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the anomalous vs. standard diffusion question can be hard to resolve using a single trajectory when one only has access to a time series spanning ≈ 1 − 5 s and measurement noise is significant relative to thermal fluctuations [18][19][20] (this noise is sometimes referred to as "localization noise" [22] in the SPT literature). Robustness against questionable localization noise assumptions is desirable since this noise is difficult to accurately quantify in many experiments [14,[22][23][24] despite its potential heavy influence on parameter estimation, hypothesis testing, and other model diagnostics [25][26][27]. In addition, methods not requiring ensemble averaging (i.e., those capable of carrying out tests with a single trajectory) are of interest since the effective dynamics experienced in vivo can be heterogeneous due to varying local micro-environments [14,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Berglund (Michalet and Berglund, 2012 that fitting a sum of normal distributions to the LogD histogram is equivalent to fitting a sum 1069 of log-normal distributions to the D histogram. We also note here, that in a theoretical study 1070 Michalet previously showed that the distribution of diffusion constants is approximately 1071…”
mentioning
confidence: 99%
“…The optimal resolution is application-dependent: single-molecule localization may not need as good a temporal resolution as for studying singlemolecule conformational dynamic using FRET, for instance. In fact, the optimal choice of temporal resolution may sometimes be counterintuitive, as in the case of diffusion coefficient measurements, where longer integration times are in general always preferable [135].…”
Section: (D) Detectors Used For Wide Field Single-molecule Imagingmentioning
confidence: 99%